Implementation of the PJBL Strategy in Improving PAI Learning Class 4 at SDN 3 Malangnengah - Imam Tabroni; Risa Siti Nurmayanti; Rini Purnama Sari (Jurnal Multidisiplin Madani, 2022)
This study aims to improve student achievement and learning activities in PAI learning in grade 4 SDN 3 through the application of Project Based Learning (PjBL) learning methods accompanied by concept maps. This research is a Classroom Action Research. The research subjects were 4th grade students of SDN 3 Malangntengah. Sources of data come from teachers and students. Data collection techniques are by test and non-test (observation, and interviews). Data analysis used descriptive qualitative analysis techniques. The results showed that the Project Based Learning (PjBL) method accompanied by a concept map in PAI learning class 4 at SDN 3 Malangnengh could improve student achievement in the cognitive aspects of student mastery.